MAKING EAU DE PARFUM FROM VANILLA AND PATCHOULI ESSENTIAL OILS BASED ON FRANGIPANI FLOWER ESSENTIAL OIL (PLUMERIA SP.) - M Syahlung Siregar; Cut Aja Rahmahwati; S Syafruddin (Politeknik Negeri Lhokseumawe, 2026)
This study aims to make Eau de Parfum based on frangipani (Plumeria sp.) essential oil by adding vanilla and patchouli essential oils as middle and base aromas. The frangipani essential oil was extracted using the soxhletation method using n-hexane as a solvent. The volume of frangipani essential oil used varied, namely 2.4 ml, 2.6 ml, 2.8 ml, 3 ml, and 3.2 ml, while the volume of vanilla essential oil varied, namely 1.2 ml, 1 ml, 0.8 ml, 0.6 ml, and 0.4 ml. The perfume formula was evaluated through specific gravity, aroma persistence, yield, composition (GC-MS), and organoleptic (homogeneity, clarity, and aroma) tests. The results showed that a volume of 3 ml of frangipani essential oil and 0.6 ml of vanilla essential oil produced the aroma most preferred by panelists, with an average specific gravity value of 0.82–0.83 g/ml, and an aroma that lasted up to 5 hours. GC-MS tests showed the presence of active compounds such as dimethyl phthalate, geranyl benzoate, and nerolidol which play a role in the stability and durability of the perfume aroma. Keywords: aroma, frangipani flower, Eau de Parfum, GC-MS, organoleptic